Room‐Temperature Magnetoelectric Coupling in Atomically Thin ε‐Fe2O3. Issue 7 (19th December 2022) - Wang, Yuzhu; Wang, Peng; Wang, Hao; Xu, Bingqian; Li, Hui; Cheng, Mo; Feng, Wang; Du, Ruofan; Song, Luying; Wen, Xia; Li, Xiaohui; Yang, Junbo; et al.
Abstract: 2D multiferroics with magnetoelectric coupling combine the magnetic order and electric polarization in a single phase, providing a cornerstone for constructing high‐density information storages and low‐energy‐consumption spintronic devices. The strong interactions between various order parameters are crucial for realizing such multifunctional applications, nevertheless, this criterion is rarely met in classical 2D materials at room‐temperature. Here an ingenious space‐confined chemical vapor deposition strategy is designed to synthesize atomically thin non‐layered ε‐Fe2 O3 single crystals and disclose the room‐temperature long‐range ferrimagnetic order. Interestingly, the strong ferroelectricity and its switching behavior are unambiguously discovered in atomically thin ε‐Fe2 O3, accompanied with an anomalous thickness‐dependent coercive voltage. More significantly, the robust room‐temperature magnetoelectric coupling is uncovered by controlling the magnetism with electric field and verifies the multiferroic feature of atomically thin ε‐Fe2 O3 . This work not only represents a substantial leap in terms of the controllable synthesis of 2D multiferroics with robust magnetoelectric coupling, but also provides a crucial step toward the practical applications in low‐energy‐consumption electric‐writing/magnetic‐reading devices. Abstract : A space‐confined CVD strategy is designed to synthesize atomically thin ε‐Fe2 O3 single crystals and disclose the room‐temperature ferrimagnetism. The strong ferroelectricity and its switching behavior are discovered in atomically thin ε‐Fe2 O3, accompanied with an anomalous thickness‐dependent coercive voltage. The robust room‐temperature magnetoelectric coupling is uncovered by controlling the magnetism with electric field and verifies the multiferroic feature of ε‐Fe2 O3 .